Thirty-day β-hydroxy-β-methylbutyrate supplementation with a controlled diet does not alter the morphological and morphometric characteristics of the rat diaphragm muscle - de Souza BUENO, Cleuber Rodrigo; MARTINELLI, Bruno; Candido BERNARDO, Gabriele; Rossi DARÉ, Leticia; Carlos ANDREO, Jesus; ROSA JUNIOR, Geraldo Marco (Revista de Nutrição, 2023)
Objective To evaluate the b-hydroxy-b-methylbutyrate supplementation infl uence on the morphological and morphometric characteristics of the diaphragm muscle of rats and verify whether there are sex differences. Methods Experimental study with 48 Wistar rats (24 of each sex) divided into 3 groups: Control Group: in which a daily diet with saline solution was offered; Experimental Group: the same amount of food from the Control group consumed in the previous day and 0.3g/kg of β-hydroxy-β-methylbutyrate; Ad libitum Experimental Group: ad libitum feeding with the same dose of the supplement. The analysis consisted of histomorphometry and classification in diaphragm muscle fiber area bands. The procedures occurred 30 days after the start of the experiment. Data were analyzed using the one-way ANOVA and Tukey tests (p<0.05). Results There was no increase in the cross-sectional area of the diaphragm muscle fibers with the supplementation protocol employed and a similar histological pattern in both sexes. No significant changes were observed in muscle fiber size ranges in the supplemented groups, suggesting that there was no hypertrophy of muscle fibers. Conclusion This study suggests that β-hydroxy-β-methylbutyrate supplementation does not cause changes in the morphological and morphometric characteristics of the diaphragm muscle, regardless of sex.